Mineral Trioxide Aggregate vs. Calcium Hydroxide in Primary Molar Pulpotomy: A Systematic Review - Shirvani, Armin; Hassanizadeh, Raheleh; Asgary, Saeed (Iranian Endodontic Journal, 2014)
Introduction: The aim of this quantitative systematic review/meta-analysis was to compare the treatment outcomes of mineral trioxide aggregate (MTA) and calcium hydroxide (CH) in pulpotomy of human primary molars. The focused PICO question was “in case of pulp exposure in vital primary molars, how does MTA pulpotomy compare to CH in terms of clinical/radiographic success?” Methods and Materials: We retrieved published randomized clinical trials (RCTs) of at least 6-month duration; our search included articles published up to March 2013 in five following databases: PubMed (Medline), Cochrane database of systematic reviews, Science Citation Index, EMBASE, and Google Scholar. Mantel Haenszel and Inverse Variance-weighted methods were applied by STATA; the relative risk (RR) was calculated with 95% confidence intervals (CI). Results: A total of 282 English articles were collected. Two authors independently screened the articles and five RCTs were selected; data extraction and quality assessment were then carried out. Four RCTs were appropriate for meta-analysis according to their follow-up times by Mantel Haenszel method. Statistically significant difference was found between success rate of MTA compared to CH, with RR=0.08 (95% CI, 0.02-0.39), RR=0.19 (95% CI, 0.08-0.46), and RR=0.38 (95% CI, 0.21-0.68) for 6-, 12-, and 24-month follow-ups, respectively. A significant difference was also observed for all included RCTs after analyses using the Inverse Variance-weighted method (RR=0.44; 95% CI, 0.27-0.72). Conclusions: Systematic review/meta-analysis of included RCTs revealed that for pulpotomy of vital primary molars, MTA has better treatment outcomes compared to CH.